A Convenient and Versatile Amino‐Acid‐Boosted Biomimetic Strategy for the Nondestructive Encapsulation of Biomacromolecules within Metal–Organic Frameworks. (3rd January 2019) - Chen, Guosheng; Huang, Siming; Kou, Xiaoxue; Wei, Songbo; Huang, Shuyao; Jiang, Shuqi; Shen, Jun; Zhu, Fang; Ouyang, Gangfeng
Abstract: Herein, an amino‐acid‐boosted biomimetic strategy is reported that enabled the rapid encapsulation, or co‐encapsulation, of a broad range of proteins into microporous metal–organic frameworks (MOFs), with an ultrahigh loading efficiency. It relies on the accelerated formation of prenucleation clusters around proteins via a metallothionein‐like self‐assembly. The encapsulated proteins maintained their native conformations, and the structural confinement within porous MOFs endowed enzymes with excellent bioactivity, even in harsh conditions (e.g. in the presence of proteolytic or chemical agents or at high temperature). Furthermore, owing to the merits of nondestructive and protein surface charge‐independent encapsulation, the feasibility of this biomimetic strategy for biostorage, enzyme cascades, and biosensing was also verified. It is believed that this convenient and versatile encapsulation strategy has great promise in the important fields of biomedicine, catalysis, and biosensing.